To solve the equation \( 5x−12−6x=−10x+7−1 \), we start by combining like terms.
Step 1: Combine like terms
On the left side:
- Combine \( 5x \) and \( -6x \): \[ 5x - 6x = -1x \text{ (or } -x\text{)} \]
On the right side:
- Simplify \( 7 - 1 \): \[ 7 - 1 = 6 \]
Now the equation looks like this: \[ -x - 12 = -10x + 6 \]
Step 2: Add \( 10x \) to both sides (to eliminate \( -10x \) on the right): \[ -x + 10x - 12 = 6 \] This simplifies to: \[ 9x - 12 = 6 \]
Step 3: Add \( 12 \) to both sides: \[ 9x - 12 + 12 = 6 + 12 \] This simplifies to: \[ 9x = 18 \]
Step 4: Divide both sides by \( 9 \): \[ x = \frac{18}{9} \] This simplifies to: \[ x = 2 \]
So, the full progression is to organize as follows:
-
Combine like terms:
- Left side becomes \( -x - 12 \)
- Right side becomes \( -10x + 6 \)
-
Add \( 10x \)
-
Add \( 12 \)
-
Divide by \( 9 \)
Final answer: \( x = 2 \)